Answer:
the answer is 22
Step-by-step explanation:
-|-7|+|-2+17
the 7 becomes positive
(7|+|-2)+17
5+17
=22
Answer:
5236
Step-by-step explanation:
let x=43
f(43)=3(43)^2-5
f(43)=3(1749)-5
f(43)=5241-5
f(43)=5236
The difference between (3x+6y)(3x+6y) and (4x+9y)(4x+9y) is 7x² +36xy+45y²
<h3>What is an Expression ?</h3>
An expression is a mathematical statement which has variables , constants and mathematical operators simultaneously.
The expression given in the question is
(3x+6y)(3x+6y) and (4x+9y)(4x+9y)
the difference when (3x+6y)(3x+6y) is subtracted from (4x+9y)(4x+9y)
(4x+9y)(4x+9y) - (3x+6y)(3x+6y)
16 x² + 36xy+36xy +81y²-9x²-18x -18x -36y²
7x² +36xy+45y²
Therefore in simplest term , The difference between (3x+6y)(3x+6y) and (4x+9y)(4x+9y) is 7x² +36xy+45y²
To know more about Expression
brainly.com/question/15245739
#SPJ1
M(x, y) = ((x1 + x2)/2, (y1 + y2)/2) = ((-2 + 4)/2, (5 - 9)/2) = (2/2, -4/2) = (1, -2)